Observational developments of the culture of big-belly seahorse, Hippocampus abdominalis (Lesson, 1827): a conservation effort for the future - Ismail, Mohamad Saupi; Yap, Chee Kong (RAFT Publications, 2019)
The objective of the present study was to document the growth and survival rates of Hippocampus abdominalis, beginning from captive-born to adulthood, and finally to the complete life cycle. The most significant finding from this culture study was that, after day 193, the life cycle of first generation of captive-born H. abdominalis in AkuaTAR was successfully observed. It is claimed that this is the first successful life cycle in captivity and production of the next generation of H. abdominalis in Malaysia. Our finding was obviously better because the survival rate was significantly higher when compared to those previously reported for this seahorse species. In short, the present observational study presented a simple culture technique that can produce optimum growth and survival through to adult stage of seahorse H. abdominalis. Hence, the present finding is important for conservation of seahorse H. abdominalis in the future.